Sistema de gestión, administrativo, contable y tributario en la distribuidora Iralda persona natural obligada a llevar contabilidad - López Molina, Maricela Elizabeth (2013)
The business environment is becoming ever more competitive, companies need to update and improve its management to ensure their permanence in the market and meet the needs of its customers. This work has as main purpose to design a management, administrative, accounting and tributary for Distribuidora Iralda commercial company dedicated to selling hardware`s goods in which administrative errors were detected, after determining its bottlenecks, it is considered necessary to implement the Balanced Scorecard, which focuses on four main areas: financial perspective, customer perspective, process perspective and learning and growth, in order to improve the working environment, standardize processes and procedures, retain and increase the customer base and generate better returns with human talent trained, motivated and loyal.